Inventory Model for Deteriorating Items Involving Trade Credit Policy in Three-Echelon Supply Chain System - D. Sharmila; R. Uthayakumar (International Journal of Mathematics And its Applications, 2016)
In present study, we generalize order linked trade credit policy in three echelon supply chain system where manufacturer, distributor and retailer are involved. Here manufacturer provide delay period to distributors also distributor provide trade credit policy to his retailers. In this paper, we discuss a three echelon supply chain system as cost minimization to determine the system's optimal cycle time. We determine the optimal order time, order quantity and optimal payment time. To investigate the effect of changes in inventory parameter values on the optimal policy, a sensitivity analysis is conducted.